Partia komunistyczna walcząca z religią i państwo komunistyczne gwarantujące wolność religijną jako teoretyczne podstawy marksizmu-leninizmu w walce z religią i Kościołem katolickim w krajach realnego socjalizmu - Jędraszewski, Marek (Poznańskie Studia Teologiczne, 2008)
Marek Jędraszewski in his article The Communist Party fighting with religion and the communist state guaranteeing religious freedom, as theoretic background for Marxism-Leninism in fight against religion and Catholic Church in the countries o f real socialism, presents philosophical and ideological principles, which direct the course of politic of communists states in the battle against religion and Church, especially Catholic Church. The author shows sources of that in antireligious thoughts of the modem Europe: deism of Enlightenment and philosophy of Feuerbach for whom the sole condition of substantial human freedom was appreciation of radical atheism. Next, author presents the Marxist conception of religion as the “opiate of the masses” and “opiate for the masses”. On the end, is presenting Lenin’s distinction between antireligious program of party and worldview neutrality of state, which was the ground for cutthroat war against religion, both in the Soviet Union and other countries of People’s democratic so-called the Ostblock) in the period 1944-1989. Author resemble the main thesis of the Pius XI encyclical Divini Redemptoris from 1939, which shows antihumanistic, furthermore felon face of “godless communism”. The best example giving by the author, for the rightness of popes words, is abatement of the Catholic Church by the communist party in the Poland in the times of Polish People’s Republic. As a conclusion author is citing words of pope John Paul II from encyclical Centesimus annus: “Marxism had promised to uproot the need for God from the human heart, but the results have shown that it is not possible to succeed in this without throwing the heart into turmoil” (CA, 24).